2019
DOI: 10.5194/tc-13-3117-2019
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of calving to frontal ablation quantified from seismic and hydroacoustic observations calibrated with lidar volume measurements

Abstract: Abstract. Frontal ablation contributes significantly to the mass balance of tidewater glaciers in Svalbard and can be recovered with high temporal resolution using continuous seismic records. Determination of the relative contribution of dynamic ice loss through calving to frontal ablation requires precise estimates of calving volumes at the same temporal resolution. We combine seismic and hydroacoustic observations close to the calving front of Kronebreen, a marine-terminating glacier in Svalbard, with repeat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
2
23
2
Order By: Relevance
“…This comparison does not show any obvious relationship, but as the observation time of 6 d is rather short, we cannot exclude the influence of environmental forcings on calving activity. Consistent with our observations, Pętlicki and Kinnard (2016) and Chapuis and Tetzlaff (2014) also found that the calving activity during their observation period of a few days was not dependent on environmental forcings, while others found an influence of ocean temperature on calving activity over seasonal timescales (Luckman et al, 2015;Schild et al, 2018).…”
Section: Relation To External Forcingssupporting
confidence: 90%
“…This comparison does not show any obvious relationship, but as the observation time of 6 d is rather short, we cannot exclude the influence of environmental forcings on calving activity. Consistent with our observations, Pętlicki and Kinnard (2016) and Chapuis and Tetzlaff (2014) also found that the calving activity during their observation period of a few days was not dependent on environmental forcings, while others found an influence of ocean temperature on calving activity over seasonal timescales (Luckman et al, 2015;Schild et al, 2018).…”
Section: Relation To External Forcingssupporting
confidence: 90%
“…For high calving activity these methods tend to miss individual events due to limited temporal resolution and their dependency on suitable weather conditions. Promising indirect methods are terrestrial photogrammetry using timelapse imagery (Minowa et al, 2018;How et al, 2019;Vallot et al, 2019), seismic monitoring (Amundson et al, 2012;Walter et al, 2013;Bartholomaus et al, 2015;Köhler et al, 2016Köhler et al, , 2019 and wave amplitudes (Minowa et al, 2018, MinowaPodolskiy et al, 2019. Nevertheless, these methods are not suitable for measuring the calving volume directly and rely on simplified assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…A low conversion efficiency is consistent with observations reported for other physical mechanisms of underwater noise generation. For example, only ∼ 10 −8 of the energy dissipated by a breaking surface wave on the ocean is radiated as sound (Loewen and Melville, 1991). Similarly, the conversion efficiency of the impact energy of a 1-5 mm scale raindrop falling on the sea surface to underwater impact noise is in the range 10 −9 to 10 −8 (see Eq.…”
Section: Relationship Between the Block-water Impact And Acoustic Energymentioning
confidence: 99%